Ruthenium(Ii)Â€“Carbonyl Complexes Containing Two N-Monodentate 1,8-Naphthyridine Ligands: Active Catalysis in Transfer Hydrogenation Reactions - Moya-Duran, S; Moya-Duran, S (Wiley-Blackwell, 2018)
The reaction of 2-aminonicotinaldehyde with 2- or 4-methoxyacetophenone in basic media leads to the new ligands 2-(4-methoxyphenyl)-1,8-naphthyridine and 2-(2-methoxyphenyl)-1,8-naphthyridine, respectively, in high yield. The reaction of these naphthyridine derivatives with [RuCl2(CO)2]n leads to the respective complexes cis-dicarbonyldichloridobis[2-(4-methoxyphenyl)-1,8-naphthyridine-ÎºN8]ruthenium(II) and cis-dicarbonyldichloridobis[2-(2-methoxyphenyl)-1,8-naphthyridine-ÎºN8]ruthenium(II), both [RuCl2(C15H12N2O)2(CO)2], in good yield. Both ruthenium(II) complexes display a slightly distorted octahedron with two cis carbonyl, two cis chloride and two cis naphthyridine ligands, the latter coordinated in a monodentate fashion through the N atom in the 8-position. Both complexes exhibit a moderate catalytic activity in the hydrogen-transfer reaction from propan-2-ol to acetophenone in the presence of a base, with 100% selectivity. Â© International Union of Crystallography, 2018